Using Nutraceuticals to Help Manage Traumatic Spinal Cord Injury - Paul Stacey; Arun Mensinkai; Pankaj Bansal; Seyed-Hossein Hosseini; Andrew Lavigne; Basia Gwardjan; Sayna Leylachian; Zhihui (Joy) Deng; Vinjamuri Chari; Sandra Giles; Shanker Nesathurai (Pharmaceuticals, 2024)
Traumatic spinal cord injury (TSCI) is a significant public health challenge that has an adverse impact on functional independence, quality of life, and life expectancy. Management of people’s chronic conditions is a key aspect of contemporary medical practice. Our study was an open label, single arm, prospective pilot study to evaluate the feasibility of treating people with TSCI. The study intervention was treatment with oral selenium and vitamin E. Participants were 18 years or older and experienced a TSCI at least one year prior to enrollment. Daily doses of 50 mcg of selenium and 400 IU of vitamin E were administered. Participants had radiologic (MRI tractography) and clinical (ASIA) assessments prior to initiating treatment, and these assessments were repeated after one year of treatment. Four subjects completed the full twelve-month study. Adherence, based on pill counts, was approximately 75% in all subjects. There were no adverse events related to study medications. During the treatment period, subjects reported improvement in certain symptoms. There was no significant difference in ASIA scores before and after the intervention. Combination treatment with vitamin E and selenium has been demonstrated as safe for TSCI patients. It is possible to use DTI values to locate the epicenter of a lesion as well as gauge the extent of injury. MRI tractography may serve as a meaningful surrogate endpoint. The results of this study suggest that it is feasible to conduct a larger long-term clinical trial to evaluate the efficacy of combination treatment of TSCI.